Ideas and Innovation in East Asia - Brahmbhatt, Milan; Hu, Albert (World Bank, 2012)
The generation, diffusion, absorption, and application of new technology, knowledge, or ideas are crucial drivers of development. The authors examine the exceptionally fast growth in domestic innovation efforts in Korea, Taiwan (China), Singapore, and China, drawing on information about R&D as well as patent and patent citations data. They also use the World Bank Investment Climate Surveys to investigate sources of technological innovation in the other middle- and low-income East Asian economies. They then evaluate the role of three main channels for knowledge flows to East Asia—international trade, acquisition of disembodied knowledge, and foreign direct investment. Results from estimating an international knowledge diffusion model using patent citations data show that, while East Asian innovations continue to draw heavily on knowledge flows from the US and Japan, citations to the same or to other East Asian economies are quickly rising, indicating the emergence of national and regional knowledge stocks as a foundation for innovation.